2017
DOI: 10.1074/jbc.m117.794537
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analysis of advanced glycation end products in the Arabidopsis proteome provides evidence for age-related glycation hot spots

Abstract: Glycation is a post-translational modification resulting from the interaction of protein amino and guanidino groups with carbonyl compounds. Initially, amino groups react with reducing carbohydrates, yielding Amadori and Heyns compounds. Their further degradation results in formation of advanced glycation end products (AGEs), also originating from α-dicarbonyl products of monosaccharide autoxidation and primary metabolism. In mammals, AGEs are continuously formed during the life of the organism, accumulate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 74 publications
5
57
0
Order By: Relevance
“…The characteristic fragment signals attributed to compounds of certain chemical classes were selected from predicted tandem mass-spectral library deposited in Human Metabolome Database (HMDB, http://www.hmdb.ca/). A search for specific diagnostic fragment ions, characteristic for different groups of metabolites revealed several chemical families, six of which could be identified-coumarine derivates (97), metabolites with phosphocholine group (527), oxylipins (26), metabolites conjugated with sugar moieties (2), fatty acid residues (63), metabolites with phosphate group (49), which could be visualized in PLS-DA and HCA models.…”
Section: Metabolomics Analysis Of Pea Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic fragment signals attributed to compounds of certain chemical classes were selected from predicted tandem mass-spectral library deposited in Human Metabolome Database (HMDB, http://www.hmdb.ca/). A search for specific diagnostic fragment ions, characteristic for different groups of metabolites revealed several chemical families, six of which could be identified-coumarine derivates (97), metabolites with phosphocholine group (527), oxylipins (26), metabolites conjugated with sugar moieties (2), fatty acid residues (63), metabolites with phosphate group (49), which could be visualized in PLS-DA and HCA models.…”
Section: Metabolomics Analysis Of Pea Seedsmentioning
confidence: 99%
“…Thereby, in comparison to the mammalian proteins, plant polypeptides demonstrated much higher numbers of AGE sites, where modifications were formed mostly via oxidative glycosylation [25]. Moreover, a significant increase of glycation levels at specific protein residues was characteristic for ageing of Arabidopsis leaves [26] and pea root nodules [27]. Not less importantly, enhanced AGE formation accompanied environmental stress [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MG-mediated loss of proteasomal activity or impaired proteostasis due to the formation of proteolysisresistant AGEs can also contribute to aging (Nigro et al, 2019). On similar lines, age-related changes have also been observed in the Arabidopsis glycated proteome (Bilova et al, 2017) and also during natural leaf senescence in winter wheat (Hav e et al, 2015), indicating the existence of age-related glycation hotspots. Together, glycation may reasonably be termed as a nonenzymatic post-translational modification marker guiding proteins to degradation and organs to senescence.…”
Section: Agingmentioning
confidence: 94%
“…The characteristic fragment signals attributed to compounds of certain chemical classes were selected from predicted tandem mass-spectra library deposited in Human Metabolome Database (HMDB, http://www.hmdb.ca/). A search for specific diagnostic fragment ions, characteristic for different groups of metabolites revealed several chemical families, six of which could be identified -coumarine derivates (97), metabolites with phosphocholine group (527), oxylipins (26), metabolites conjugated with sugar moieties (2), fatty acid residues (63), metabolites with phosphate group (49), which could be visualized in PLS-DA and HCA models. The results clearly indicated that metabolites, featured with a phosphocholine group (most probably phosphatidylcholines), and oxylipins are more represented in the seeds of the drought-treated plants in comparison to those from controls.…”
Section: Figurementioning
confidence: 99%